Economic development and prospects of the OECS setting and overview : draft - Lestrade, Swinburne (OECS CastriesLC, 1987)
Reviews economic structure of OECS countries focussing on the monocultural nature of their production structures and also their dependence on tourism. Identifies 5 characteristics which mark the dependence of the OECS states eg. the continuing demand at good prices for raw agricultural produce on the part of the buying countries; structural rigidities in their public finance systems and also within their economic and social systems. Focusses on the economic growth of OECS states looking briefly at sectors contributing to the GDP viz. government services, agriculture, manufacturing, banking and insurance, real estate and housing.